2003
DOI: 10.3168/jds.s0022-0302(03)73927-7
|View full text |Cite
|
Sign up to set email alerts
|

Milk Fatty Acid Composition of Cows Fed a Total Mixed Ration or Pasture Plus Concentrates Replacing Corn with Fat

Abstract: Thirty-one Holstein cows (six ruminally cannulated) were used to evaluate milk fatty acids (FA) composition and conjugated linoleic acid (CLA) content on three dietary treatments: 1) total mixed rations (TMR), 2) pasture (Avena sativa L.) plus 6.7 kg DM/d of corn-based concentrate (PCorn), and 3) pasture plus PCorn with 0.8 kg DM/d of Ca salts of unsaturated FA replacing 1.9 kg DM/d of corn (PFat). No differences were found in total (22.4 kg/d) or pasture (18.5 kg/d) dry matter intake, ruminal pH, or total vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
64
3
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 23 publications
20
64
3
10
Order By: Relevance
“…The effect of diet on the FA profile is consistent with the literature (Chilliard et al, 2001;Hurtaud et al, 2002;Schroeder et al, 2003;Couvreur et al, 2006a and. The large increase in C18:1 is probably due to a greater mobilization of the lipidic reserves with the LowGS diet (Chilliard et al, 2001).…”
Section: Discussionsupporting
confidence: 87%
“…The effect of diet on the FA profile is consistent with the literature (Chilliard et al, 2001;Hurtaud et al, 2002;Schroeder et al, 2003;Couvreur et al, 2006a and. The large increase in C18:1 is probably due to a greater mobilization of the lipidic reserves with the LowGS diet (Chilliard et al, 2001).…”
Section: Discussionsupporting
confidence: 87%
“…The concentration of oleic acid and its different cis/trans isomers (including trans-10 C 18:1 ) significantly (P < 0.05) increased in the milk fat of cows supplemented with VO as a likely consequence of the rumen biohydrogenation process of linoleic and linolenic FA present in the diet and due to the desaturation of stearic acid in the mammary gland [4]. These results are globally supported by data reviewed by Schroeder et al [17] and by the works of Murphy et al [11], Lawless et al [9], Vidaurreta et al [20] and Schroeder et al [16], leaving cows feeding on pasture. All these authors used oleaginous seeds treated or not, or calcium salts of fatty acids (CaFA), which provide a reduced degree of protection of long chain unsaturated fatty acids to the biohydrogenation in the rumen.…”
Section: Resultssupporting
confidence: 81%
“…Despite the fact that the oils used in this study were good sources of linoleic acid, its increase in milk fat of supplemented cows, though statistically significant (P < 0.05), was low, suggesting a modest transfer efficiency of this fatty acid from vegetable oils to milk fat and a high rate of rumen biohydrogenation. Using fullfat rapeseeds (FFS), full-fat soybeans (FFR) or CaFA which provide some protection from rumen biohydrogenation, other authors observed a two fold increase in linoleic acid concentration in milk fat of grazed cows (4.9 g·100 g -1 FA) [9,11,16]. Unlike what happens with diets composed of conserved forage and variable proportions of concentrates, there is less information in the literature concerning the effect of oils or vegetable seed supplementation of diets on the concentrations of CLA and TVA in the milk fat of grazing dairy cows.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The uptake of some specific preformed FA (e.g., trans-10, cis-12 clA and trans-8, cis-10 CLA) reduce the activity and/or expression of genes that encode important enzymes involved in uptake, synthesis and desaturation of FA in the mammary gland (Chilliard et al 2000). In a previous study using the same source of cSFA fed to grazing cows, milkfat concentration was reduced (-26% in respect to the Control group) with no negative effect on NDF digestion (Schroeder et al 2003). In pasture-fed MC, milkfat concentration was decreased 43% by the abomasal infusion with 40 g day -1 of a clA mixture, reducing the energy requirements for lactation (13%) and increasing milk yield (11%; Mackle et al 2003).…”
Section: Milk Production and Compositionmentioning
confidence: 99%